Analyzing the Topological Structure of the eBay Negotiations' Network - França, Cinthya de M.; Rocha, Antonio A. de A.; Velloso, Pedro B. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
The OSN's (On-line Social Networks) have reached an incredible popularity in modern Internet. Those systems have been present in the daily lives of countless people helping them to share personal experiences, expectations and opinions. So high popularity has made of such networks complex systems. To understand the operation and phenomena that occur in such networks, there are metrics and models that capture aspects of their structures. The purpose of this work is to understand the complex reality of eBay ecommerce network, their connections and the dynamics of its users. Data were collected using a script developed in this work, and it resulted in a database of approximately 87 million transactions and 15 million different dealer users. From these data, the characterization was made estimating network metrics, like dealer users' degree distribution, that gave us key insights about the eBay negotiation network. We found that there are users who bought/sold for more than 100.000 different persons. We also found that a user A interacted over 4.000 times with another user B in just 3 months. Those and other interesting results, such as average distance and feedbacks ratings, were obtained, analyzed and discussed in this work.